The Effect of Silane Treatment on Interfacial Shear Strength and Wettability ofLuffa Cylindrica Fiber - Ridho Al Islam; Wijang Wisnu Raharjo; wibowo - (Jurnal Inovasi Mesin, 2025)
Luffa cylindrica, a plant from the Cucurbitaceae family, is abundant but remains underutilized. Its simple fiber extraction and high cellulose content make it a potential eco-friendly reinforcement material for composites. This study examines the effect of silane concentration on the interfacial shear strength (IFSS) and wettability of Luffa cylindrica fibers. The fibers were treated with silane solutions at concentrations of 0.5%, 1%, and 1.5%. Tests included IFSS, wettability, and SEM analysis. Results show that silane treatment improves both IFSS and wettability, with the highest values obtained at 0.5% concentration (3.68 MPa and 43.94 mN/m, respectively). SEM observations confirmed better fiber–matrix adhesion at this concentration, where multiple matrices were attached and embedded on the fiber surface. These findings highlight the potential of silane-treated Luffa cylindrica fibers as effective reinforcements for composites